Identification and Validation of a Prognostic Signature for Prostate Cancer Based on Ferroptosis-Related Genes - Liu, Huan; Gao, Lei; Xie, Tiancheng; Li, Jie; Zhai, Ting-shuai; Xu, Yunfei (Frontiers in Oncology, 2021)
Ferroptosis, an iron-dependent form of selective cell death, involves in the development of many cancers. However, systematic analysis of ferroptosis related genes (FRGs) in prostate cancer (PCa) remains to be clarified. In our research, we collected the mRNA expression profiles and clinical information of PCa patients from TCGA and MSKCC databases. The univariate, LASSO and multivariate Cox regression method were performed to construct prognostic signature. Seven FRGs, AKR1C3, ALOXE3, ATP5MC3, CARS1, MT1G, PTGS2, TFRC, were included to establish the risk model, which was validated in MSKCC dataset. Subsequently, we found that high risk group was strongly correlated with copy number alteration load, tumor burden mutation, immune cell infiltration, mRNAsi, immuetherapy and bicalutamide response. Finally, it was identified that overexpression of TFRC could induce proliferation and invasion in PCa cell lines in vitro. These results demonstrated that this risk model could accurately predict prognosis, suggesting that FRGs are promising prognostic biomarkers and drug target genes for PCa patients.